A Hybrid Artificial Photocatalysis System Splits Atmospheric Water for Simultaneous Dehumidification and Power Generation. Issue 51 (24th October 2019) - Yang, Lin; Ravi, Sai Kishore; Nandakumar, Dilip Krishna; Alzakia, Fuad Indra; Lu, Wanheng; Zhang, Yaoxin; Yang, Jiachen; Zhang, Qian; Zhang, Xueping; Tan, Swee Ching
Abstract: A new approach for artificial photocatalysis of electrical generation directly from atmospheric water is reported. A hybrid system comprising a hydrogel incorporated with Cu2 O and BaTiO3 nanoparticles is developed, wherein the Cu2 O is designed to expose two different crystal planes, namely (100) and (111). These planes exhibit different surface potentials and form a polarization electric field of 2.3 kV cm −1 that acts on a ferroelectric dipole. With the help of this electric field, the dipole is redirected for aiding in positive and negative polarizations with (100) and (111) planes, then boosting water reduction and oxidation kinetics separately at (100) and (111) planes. Additonally, zinc‐/cobalt‐based superhygroscopic hydrogels serve as a water‐capturing "hand" to harness humidity from the ambient environment. The integrated hydrogel–Cu2 O@BaTiO3 hybrid is used to dehumidify air, which can split 36.5 mg of water by employing only 150 mg hydrogel and simultaneously generate a photocurrent of 224.3 µA cm −2 under 10 mW cm −2 illumination. Abstract : A superhygroscopic hydrogel harvests humidity from the atmosphere directly and transfers the water to (100)/(111) Cu2 O@BaTiO3 nanoparticles for light‐driven water splitting. The surface potential gap of the nanoparticles can orientate the ferroelectricity, leading to water reduction at the (100) plane, while the water oxidation takes place at the (111) plane, thereby splitting atmospheric water for dehumidification and power generation.